The effect of annealing time on p-n junction diode and its device Characteristics / Nur Syazana Mohd Zainiyuddin - Mohd Zainiyuddin, Nur Syazana (2010)
The execution of this project is to investigate the effect of annealing time on p-n junction diode and its device characteristics. The parameters that were observed are dopant distributions during diffusion doping process, the optimum annealing time and current-voltage characteristic of a typical diode. The methodology was carried out using n-type diffusion furnace where the junction depth of diffused p-type dopant into silicon substrate for junction formation is observable. Factor affecting dopant distribution is investigated. The current-voltage characteristic of p-n junction diode in electrical testing is observed and analyzed. By introducing high temperature to the silicon surface during annealing process, it gave effect to dopant distribution where dopants diffused into silicon substrate which changed the conductivity of the semiconductor. Thus, through a process of doping this dopant increased the conductivity of the semiconductor. Therefore, p-n junction is formed and the ideal p-n junction characteristic is obtained. On the other hand, the optimum annealing time during fabrication process was found in producing the ideal p-n junction diode.